Moderat tilbageslag på boligmarkedet - Svend Greniman Andersen; Agnete Gad Knudsen; Simon Juul Hviid (Danmarks Nationalbank, 2020)
– The corona epidemic has caused a temporary reduction in housing market activity and a small drop in housing prices. However, stimulus packages and low interest rates continue to stimulate the demand for housing. Limited price decreases are therefore expected in 2020, and the price level is forecasted to rebound during 2021. Also, most owner-occupied dwellings have relatively low debt ratios, and only a small fraction of home buyers have been employed in industries that are currently very exposed.
Keywords: 330; Immobilienmarkt; Coronavirus; Dänemark